2019
DOI: 10.1111/psyp.13343
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cognitive load on the dynamics of neurophysiological adjustments during fatiguing exercise

Abstract: We aimed to determine the neurophysiological mechanisms associated with reduced endurance performance during cognitive‐motor dual task at different levels of cognitive load, compared to a motor task alone. Eighteen healthy men performed isometric quadriceps contractions at 15% of maximal voluntary contraction (blocks of 170 s interspaced by neuromuscular evaluations) until exhaustion. This task was performed on three separate days: (a) in the absence of concomitant cognitive task, (b) with concomitant 1‐back t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 49 publications
1
30
1
Order By: Relevance
“…submaximal handgrip and concomitant mental-math task) compared to the motor task performed alone. Moreover, Chatain et al [98] found a greater decrease in VA during a fatiguing cognitive-motor dual task (i.e. intermittent isometric quadriceps contractions with concomitant n-back task) compared to the motor task alone.…”
Section: Functional Muscular Alterations Following Downhill Runningmentioning
confidence: 99%
“…submaximal handgrip and concomitant mental-math task) compared to the motor task performed alone. Moreover, Chatain et al [98] found a greater decrease in VA during a fatiguing cognitive-motor dual task (i.e. intermittent isometric quadriceps contractions with concomitant n-back task) compared to the motor task alone.…”
Section: Functional Muscular Alterations Following Downhill Runningmentioning
confidence: 99%
“…Mehta and Parasuraman (2014) found that performing an acute mental task (approximately 3 min) during submaximal fatiguing handgrip contractions had no effect on endurance time but there was a decrease in cerebral oxygenation (prefrontal cortex) at exhaustion compared to performing fatiguing handgrip contractions alone [5]. Chatain et al (2019) showed that performing both high and low mental exertion tasks (approximately 16 min) during isometric knee extension (at 15 % of MVC) decreased exercise tolerance more than isometric knee extension alone [12]. Also, Holgado et al (2019) found that when trained and experienced cyclists performed a 20 min low or high cognitive task (1-back or 2-back) during self-paced cycling exercise there was no effect on physical performance or RPE [13].…”
Section: The Effects Of Performing Mental Exertion During Cycling Exementioning
confidence: 99%
“…Relevant scholars use the processing of Doppler radar and physiological signals to obtain fatigue parameters such as the athlete's mood change and blink frequency to determine whether the athlete is dozing off [12]- [14]. By making these devices into small devices and installing them above the athletes' heads, the athletes' normal sports activities will not be affected during the exercise [15]. Researchers have developed a device for detecting fatigue based on the physiological signals of athletes [16]- [18].…”
Section: Introductionmentioning
confidence: 99%